Dinamika Konflik Internal Kadipaten Pakualaman Di Tengah Isu Keistimewaan Daerah Istimewa Yogyakarta - Dipopamiak, Edyprono; Windiani, Reni; Utomo, Susilo (Journal of Politic and Government Studies, 2013)
The title of this thesis is Dynamics of Internal Conflict in the Duchy Pakualaman onthe Yogyakarta Privileges Issues. This background of research for the phenomenon of a conflictin one of the most influential indigenous units in Special Region of Yogyakarta (DIY) where isthe passing of the debate on the status of the privilege in Yogyakarta. Kadipaten Pakualamanas one of the most influential, suffered internal divisions due to differences in views on thePrivileges Yogyakarta and the struggle for the throne as Paku Alam IX.Based on the above formulation of this study aims to determine the Dynamics ofInternal Conflict Kadipaten Pakulaman at the same time of the passing of the DIY Privilegesissues the enactment of Law No.13/2012 about Privileges DIY where is sets Sultan and PakuAlam Hamengkubuwono as a regional head in DIY. However, the conflict in which the kingtwin is more complex at Paku Alam are not only fighting over the throne but also the positionof the deputy governor of DIY.The formulation of the problem posed in this research is "How does that happen onDynamics of Internal Conflict in the Kadipaten Pakualaman as a result of KPH Anglingkusumodisobedience attitude and underlying factors such insubordination in 2012".The Authors in conducting this study is used descriptive analytic methods andtechniques of data taken is collect documentation and interview. Data processing also used anInteraktive model methods.The results of this research, were made known the conflict occurs because of asuccession of Paku Alam who didn’t go smoothly in 1999, the distrust factors between theinternal relatives in the Kadipaten Pakualaman Castle, indications of the intervention of outsideparties into the conflict to influence issues of privilege and the motive power of the rebellionundertaken.Keywords: Privilege, Internal Conflict, Disobedience